Lived Experiences of Filipino J-1 Exchange Teachers in a Rural School District in South Carolina: An Interpretative Phenomenological Analysis - Aguilos, Bartolome (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the lived experiences of Filipino J-1 exchange teachers in a rural school district in South Carolina, focusing on their transition, professional work, challenges, coping strategies, and meanings of thriving and surviving. The study was anchored in Differential Adaptation Theory, the Ecological Perspective on Emotional Vulnerability and Professional Identity Construction, and the Professional Identity Reconstruction Framework. It employed a qualitative research design using Interpretative Phenomenological Analysis. Six Filipino J-1 exchange teachers who had completed at least one academic year in the district were selected through purposive, criterion-based sampling. Data were collected through one-on-one, semi-structured, in-depth interviews and analyzed through case-by-case and cross-case interpretative procedures. The findings revealed that transition involved professional relearning, cultural adjustment, emotional endurance, and teacher identity reconstruction. Major challenges included student behavior, classroom management, language and accent differences, parent communication, family separation, rural transportation, financial concerns, and emotional strain. Participants coped through patience, openness, self-reflection, continued learning, family communication, Filipino peer networks, mentoring, school leadership, and district support. Thriving and surviving were experienced simultaneously, as participants developed confidence, resilience, belonging, and professional growth while continuing to manage uncertainty and pressure. The study concluded that sustained, context-based support is necessary and recommended a year-long program covering induction, classroom management coaching, communication assistance, mentoring, well-being support, rural living guidance, transportation assistance, financial orientation, and settlement support. The study primarily supports SDG 4 on Quality Education and is also connected to SDG 8 on Decent Work and SDG 17 on international educational partnerships. Its sustainability impact lies in strengthening teacher well-being, retention, instructional continuity, inclusive school environments, and responsive institutional support for internationally mobile educators.
Keywords: Cross-Cultural Adaptation; Filipino J-1 Exchange Teachers; Interpretative Phenomenological Analysis; Professional Identity Reconstruction; Rural Education; Teacher Support; Teacher Well-Being; Thriving and Surviving